Potential of blockchain technology for trade integration of developing countries - Jakob Schwab; Jan Ohnesorge (Deutsches Institut für Entwicklungspolitik (DIE), 2019)
Blockchain technology (BT), famous due to its use in digital currencies, also offers new opportunities in other fields, one of which is trade integration. Developing countries especially could benefit from greater trade integration with BT, as the technology can, for example, remedy deficiencies with regard to financial system access, intellectual property protection and tax administration. BT allows virtually tamper-proof storage of transactions and other data on decentralised computer networks. In fact, it is possible to store not only data, but also entire programmes this securely: Smart contracts enable the automation of private transactions and administrative processes. This article summarises the latest research on the use of BT in trade integration by examining in more detail five key and, in some cases, linked fields of application. The first is trade finance, where BT could deliver direct cost savings for exporters and importers by removing the need for credit-lending intermediaries. Second, tamper-proof storage of information on the origin and composition of goods could enhance supply chain documentation. This makes it possible to more reliably verify compliance with sustainability standards, particularly for globally produced goods. However, for the information in blockchains to be truthful, it must be entered correctly (it is then tamperproof), a process that therefore requires monitoring. Third, BT could deliver improvements in the field of trade facilitation by making it easier for border authorities to access information on goods and thus easing reporting requirements for exporting firms. By reducing dependence on central database operators, BT could help bring about a breakthrough with existing digital technology in the area of trade. Fourth, facilitating access to information on goods could also simplify customs and taxation procedures and make them less vulnerable to corruption and fraud. This goes hand in hand with cost reductions for exporters and better mobilisation of domestic resources for public budgets. Fifth, in the field of digital trade, BT also facilitates management of digital file rights in environments where, for institutional reasons, there is little intellectual property protection. This could help to promote digital industries in developing countries. However, when it comes to using BT in border and customs systems in particular, it is essential to involve the relevant authorities at an early stage. At the same time, it is necessary to promote uniform technical standards for supply chain documentation in order to safeguard interoperability between the different systems across actors and national borders and thus fully leverage the cost advantages. If these guidelines are taken into account, then BT could effectively support sustainable trade integration of developing countries.
Keywords: 330; Digitalisierung; Handel und Investitionen